Nivel de conocimientos sobre vasectomía en los habitantes del barrio Cascajal del cantón Calvas de la provincia de Loja. - Ramos Pardo, Juan Gabriel (2013)
34. A problem in the rural male population is the non-acceptance in health coverage, family planning and low engagement in science, which could be due to lack of information and sociocultural factors. The present study had as objectives; establishing a diagnosis of vision with local residents in study versus vasectomy, to determine the sociodemographic characteristics of men subject of study, to identify the level of education in relation to vasectomy, and to describe the factors that influence the acceptability of this method of contraception. So that, I performed ​​a cross-sectional descriptive study with a sample of 60 men of Cascajal neighborhood that obeyed the criteria for inclusion, using a previously developed survey, obtaining as results : that the predominant age range was 30 to 39 years old with 50% , 38.3 % were married , 58.3 % have a primary education level and the predominant occupation was agriculture with 36.6 % , 78.3 don’t have profession , 100% are Catholic , 51.6 % don’t have a clear idea of ​​vasectomy and only 28.3 % have an adequate knowledge , 51.6 % don’t know what is the use of vasectomy , 60 % of the study population have not received information about vasectomy, while 40 % have received information, through comments friends, family and reading , 85 % think that the issue of family planning is only for women , in the same way 65% would not practice a vasectomy and 61.6 % explained that the reason why they would practice the vasectomy would be the number of children , 100% are agree that as men they should decide if they want to have children , as well as 85 % think that they would have sexual impotence if they tested to the procedure , while only 15 % think that they would not have any problem if they have one. Keywords: Vasectomy, Family planning, knowledge.